Presence of an Isolated Hydatid Cyst in the Left Kidney: Report of a Case of This Rare Condition Managed Surgically. (27th June 2016) - Paramythiotis, Daniel; Bangeas, Petros; Kofina, Konstantinia; Papadopoulos, Vassileios; Michalopoulos, Antonios
Abstract : Introduction. Hydatid cyst disease caused by Echinococcus granulosus is rarely presented in the kidneys, whereas isolated renal occurrence is estimated to be about as low as 2–4% of all cases. We present a case of a female patient suffering from this condition that was treated successfully in our department. Case Presentation. A 44-year-old woman was incidentally diagnosed with a 14 cm left renal cystic mass through ultrasound imaging performed during upper abdominal pain investigation. Laboratory examinations were normal and CT imaging set the diagnosis of an isolated left renal hydatid cyst. The cyst was excised and the postoperative period was uneventful. Discussion. Isolated renal hydatid cyst is a very rare condition and could possibly be misdiagnosed with other renal masses. The clinical history, laboratory tests, and thorough radiologic imaging are crucial for the accurate preoperative diagnosis.